Leukemia cell-derived microvesicles induce T cell exhaustion via miRNA delivery. (3rd July 2018) - Cui, Jieke; Li, Qing; Luo, Mei; Zhong, Zhaodong; Zhou, Shu; Jiang, Lin; Shen, Na; Geng, Zhe; Cheng, Hui; Meng, Li; Yi, Shujuan; Sun, Hui; et al.
ABSTRACT: T cell function in cancer patients is usually impaired due to the constitutive activation of immune checkpoint inhibitors. This state is known as 'exhaustion' and is often associated with the inefficient control of tumors or persistent infections. In this work, we investigated the role of leukemia cell-derived microvesicles (MVs) in T cell exhaustion. Following incubation with MVs from various sources, all T cell subtypes exhibited the exhaustion phonotype and impaired cytokine secretion in vitro. Mice models also showed the connection between immune checkpoint inhibitors and MV injection. Sequencing and bioinformatics analyses indicated that a number of transcription factors and microRNAs (miRNAs) were attributable to the dysregulation of pathways and exhaustion in T cells. Further work revealed that functional miR-92a-3p, miR-21-5p, miR-16-5p, miR-126 and miR-182-5p in MVs could be delivered into T cells to induce the exhaustion phenotype. SerpinB2, IL-1β and CXCL5, which are mediators of the NF-κB pathway, were identified as the targets of the miRNAs mentioned above. We demonstrated that leukemia-derived MVs could initiate T cell exhaustion via the progressive temporal delivery of multiple exogenous miRNAs into T cells and the subsequent interaction of these miRNAs with their targets. Therefore, MVs can be expected not only to become new indicators of the T cell status in patients but also to be used as novel targets for personalized patient treatment.